Unmanned aerial vehicles and multidisciplinary applications using AI techniques - Thusnavis, Mary Bella I., 1985-; Sagayam, K. Martin, 1987-; Elngar, Ahmed A. (Advances in computational intelligence and robotics (ACIR) book series., 2022)
"This comprehensive edited book covers Artificial techniques, pattern recognition, machine and deep learning--based methods and techniques applied to different real time applications of unmanned aerial vehicles (UAV) with the goal to synthesize the scope and importance of machine learning and deep learning models in enhancing UAV capabilities, solutions to problems and numerous application areas"--